Inter-professional physician-nurse collaboration in Lebanon. Issue 1 (3rd October 2019) - Ahmadieh, Hala; Majzoub, Ghali H.; Abou Radi, Faraj M.; Abou Baraki, Areej H.
Abstract : Purpose: A physician–nurse relationship is a complex, professional and shared-decision-making process, which is an important predictor of high-quality patient care. The purpose of this paper is to explore the attitude of the physician–nurse relationship in Southern Lebanon hospitals. Design/methodology/approach: A descriptive institutional cross-sectional study was conducted among different departments of three hospitals in Southern Lebanon using a validated Jefferson Scale of Attitude. Findings: In sum, 89 physicians and 245 nurses accepted to participate. The nurses' mean age was 32 and the physicians' was 44. The mean score was found to be 46 for all participants, with significantly higher scores noted among nurses compared to physicians (48 vs 43, respectively) and higher scores among females compared to males (48 vs 46, respectively). However, the study scored no significant difference in relation to the degrees attained by nurses and the participants' years of experience. The majority had agreed that the shortage in the nurses' staff affects proper patient care delivery. One fourth of the physicians disagreed that nurses should be considered as a collaborator and colleague. Therefore, more work is required to improve this collaboration. Research limitations/implications: There is a complex relationship normally displayed by physicians and nurses, which cannot be easily interpreted and analyzed. Physicians and nurses may have given socially desirable responses while filling the questionnaire. Even more, this study was conducted in Hospitals in Southern Lebanon, and it would be nice to extend this study to include further hospitals in other regions in Lebanon as well. Practical implications: Nurses had higher scores toward collaboration, with females scoring higher than males. However, overall scores are considered to be lower compared to other countries. Thus, more efforts should be done on improving this communication among nurses and physicians, through promoting inter-professional undergraduate and postgraduate education training toward more effective communication. Social implications: Quality of patient care would be improved if more work is done on improving the collaboration between physicians and nurses, and this was shown to be required as per study results. Originality/value: There is a gap in literature assessing this important topic which is the collaboration and attitude of nurses and physicians toward their relationship in Lebanon. It is extremely important that efforts should be taken in order to determine the type of nurse–physician relationship in every local context as this relationship affects quality of patients' care.